Pengelolaan Bank Sampah di Kota Probolinggo - Prisa Ambar Shentika (Jurnal Ekonomi dan Studi Pembangunan, 2016)
A programme of reducing garbage leads the community, government, and corporate field to attentively limit the trash heap, recycling, and reusing garbage through the efficient and well-regulated efforts commonly called 3R Reduce, Reuse, Recycle. Probolinggo is the town in which developing regulate a policy of management garbage with Waste Bank by 3R concepts. This research aims to find out the management and role of Waste Bank in Probolinggo. It is conducted by using qualitative descriptive research method. Data collection is obtained by using direct observation and interview to resource. The result shows that 3R concepts used by waste bank in Probolinggo is carried out fairly well in working along with society particularly in sorting the garbage. Therefore, aware of environmental issues is not on government but society will cooperatively in role to protect environment. Waste bank is economically good for society beside environmentally worthwhile.